The Differences of Analytical Thinking Skills on Biodiversity Material in Guided Inquiry Model with Conventional Class - Rama Cahyati; Bambang Subali (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to compare whether there are differences in analytical thinking skills between classes that use guided inquiry models and conventional classes that use discussion methods and to find out whether guided inquiry models can improve analytical thinking skills in class X SMA. This type of the research is a quasi experimental research that uses a pretest posttest control group design. The population of this research were students of class X SMA Negeri 1 Kalasan and class X SMA Negeri 1 Prambanan. The sample in this research were 4 classes with a total of 104 students. Sampling in this research was conducted by cluster random sampling. The results of the t test obtained the value of sig. (2-tailed) of 0.000, the probability value is less than 0.05, which means that there are differences in analytical thinking skills in the guided inquiry class and the conventional class. The gain score test results obtained a value of 0.71 with a high category, meaning that the use of the guided inquiry model can improve analytical thinking skills in class X SMA